HUBUNGAN ANTARA SARAPAN DENGAN TINGKAT KONSENTRASI PADA MAHASISWA ANGKATAN 2011 DI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - I.G.N Bagus Hindra D; I Dewa Ayu Inten Dwi Primayanti (Universitas Udayana, 2017)
Concentration is part of cognitive function. Concentration makes people can focus in doing something in the given time. There are many things that can influence concentration. This study was conducted to know the relationship between breakfast and the degree of concentration in teenager. This study is analytic observational study with cross sectional approach. The samples was taken with consecutive sampling method. The samples in this study was from 2011 college student in Medical Faculty of Udayana University which is either doing breakfast or not, and willing to participate in this study by signing the informed consent. From 83 samples, 56 was doing breakfast and 27 was not. After the test using Continuous Performance Task (CPT) was done, we found the number of people which have good concentration in breakfast group are 12 and 44 have bad concentration in breakfast group. Meanwhile in non breakfast group, one has good concentration, and 70 have bad concentration. After the hypothesis testing was done with fischer method, we get the p>0.05 which show that there are no difference in the degree of concentration between breakfast and non breakfast group. Thus, it is concluded that there is no relationship between breakfast and the degree of concentration. The results of this research could be applied as a basis for further research in searching factors that can influence the degree of concentration. Keywords : Breakfast, concentration, Continuous Performance Task